A Prospective Study of Acute Blood‐Based Biomarkers for Sport‐Related Concussion. Issue 6 (20th April 2020) - Meier, Timothy B.; Huber, Daniel L.; Bohorquez‐Montoya, Luisa; Nitta, Morgan E.; Savitz, Jonathan; Teague, T. Kent; Bazarian, Jeffrey J.; Hayes, Ronald L.; Nelson, Lindsay D.; McCrea, Michael A.
Abstract : Objective: Prospectively characterize changes in serum proteins following sport‐related concussion and determine whether candidate biomarkers discriminate concussed athletes from controls and are associated with duration of symptoms following concussion. Methods: High school and collegiate athletes were enrolled between 2015 and 2018. Blood was collected at preinjury baseline and within 6 hours (early acute) and at 24 to 48 hours (late acute) following concussion in football players (n = 106), matched uninjured football players (n = 84), and non–contact‐sport athletes (n = 50). Glial fibrillary acidic protein, ubiquitin c‐terminal hydrolase‐L1, S100 calcium binding protein B, alpha‐II‐spectrin breakdown product 150, interleukin 6, interleukin 1 receptor antagonist, and c‐reactive protein were measured in serum. Linear models assessed changes in protein concentrations over time. Receiver operating curves quantified the discrimination of concussed athletes from controls. A Cox proportional hazard model determined whether proteins were associated with symptom recovery. Results: All proteins except glial fibrillary acidic protein and c‐reactive protein were significantly elevated at the early acute phase postinjury relative to baseline and both control groups and discriminated concussed athletes from controls with areas under the curve of 0.68 to 0.84. The candidate biomarkers also significantly improved the discrimination of concussed athletes from noncontact controls compared to symptom severity alone. Glial fibrillary acidic protein was elevated postinjury relative to baseline in concussed athletes with a loss of consciousness or amnesia. Finally, early acute levels of interleukin 1 receptor antagonist were associated with the number of days to symptom recovery. Interpretation: Brain injury and inflammatory proteins show promise as objective diagnostic biomarkers for sport‐related concussion, and inflammatory markers may provide prognostic value. ANN NEUROL 2020;87:907–920